Multi-point joint power analysis attack against AES - Zhi-bo DU; UNYuan-hua S; ANGYi W (Tongxin xuebao)
For the power analysis attack of the AES cryptographic algorithm with the single information leakage point,the traditional attack method does not use as much information as possible in the algorithm and power trace.So there are some problems such as required more power traces,the low utilization rate of information and so on.A novel method of muti-point joint power analysis attack against AES was proposed to solve the problems.And taking the correlation power analysis attack as an example,the detailed attack process was presented.The operations of the round key addition and the SubBytes were chosen as the attack intermediate variable at the same time.Then the joint power leakage function was con-structed for the attack intermediate variable.And the multi-point joint correlation energy analysis attack was given.Aiming at the AES cryptographic algorithm implemented on the smart card,the multi-point joint power analysis attack,the correlation power analysis attack with the single information leakage point in the key addition and the SubBytes were conducted.The measured results validate the proposed method is effective.It also shows that the proposed method has the advantages of high success rate and less power traces comparing with the single information leakage point.